PERAN ORANG TUA TERHADAP PEMELIHARAAN KESEHATAN GIGI DAN MULUT PADA ANAK USIA DINI DI POS PAUD MELATI PAGERWANGI LEMBANG KABUPATEN BANDUNG BARAT (Politeknik Kesehatan Kemenkes Bandung, 2021)
Of child development the knowledge of people, especially woman in dental preservation, has a significant influence on oral and dental health in children, because mother’s are the people closest to children research objectives. The participation of every parent will create the success of children’s dental care requires. Parent’s role as a figure and as role models will provides a good example for children in performing dental health care. Research Objective : The purpose of this study is to know the role of parent’s in maintaining oral health in reminding and teaching early childhood at POS PAUD Melati Pagerwangi Lembang. Research Method : The method of this research is descriptive study by do a filling out a questionnaire. Sampling was done by total sampling consisted of 32 mother’s at POS PAUD Melati Pagerwangi and analyzed using a frequency distribution table. Research Result : The result of this study show indicate that 23 respondents (71.9%) have a good role in maintaining dental and oral health in early childhood. This is because the mother's highest education level is high school (46.9%) and (56.3%) the mother's job is housewife. Conclusion : Based on the results of the study with a sample of 32 respondents from parent’s (mother’s) at POS PAUD Melati Pagerwangi, it can be concluded that as many as 23 respondents (71.9%) already have a good role in maintaining oral health in their children. A total of 8 respondents (25%) have a enough role. A total of 1 respondent (3.1%) have a bad role.